2005
DOI: 10.1111/j.1600-6143.2005.00773.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful Liver and Kidney Transplantation From Cadaveric Donors With Left-Sided Bacterial Endocarditis

Abstract: Bacterial infections are frequent in cadaveric organ donors and can be transmitted to the transplantation recipient, which could have devastating consequences for the recipients if adequate preventive measures are not adopted. Infection by the bacteria responsible for the endocarditis in the respective donors was not transmitted to any of the recipients. Six of the seven recipients were alive with normal-functioning grafts after between 13 and 24 months' follow-up. Transplantectomy was performed on one kidney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 29 publications
(45 reference statements)
0
25
0
1
Order By: Relevance
“…Multiple retrospective studies have demonstrated the safety of transplanting livers that were procured from donors with bacterial infections (96). Organs have been successfully transplanted from donors with Gram-positive endocarditis and bacteremia with no effect on 1-year survival (293,294). Liver transplantation has also been successful utilizing grafts from donors with active meningitis (105).…”
Section: Recommendationsmentioning
confidence: 98%
“…Multiple retrospective studies have demonstrated the safety of transplanting livers that were procured from donors with bacterial infections (96). Organs have been successfully transplanted from donors with Gram-positive endocarditis and bacteremia with no effect on 1-year survival (293,294). Liver transplantation has also been successful utilizing grafts from donors with active meningitis (105).…”
Section: Recommendationsmentioning
confidence: 98%
“…Furthermore, a recent report showed few cases of successful transplantation of donor organs (liver and kidney) retrieved from donors with left-sided bacterial endocarditis [40]. The role of donor related pneumonia especially in lung and heartlung transplantation seems to be less important.…”
Section: Patientmentioning
confidence: 97%
“…Kidney and liver transplants were made from these donors with cultureguided antibiotic therapy, with no recipient infectionrelated complications (C). (82) Similarly, a donor who died from Naegleria fowleri amoebic meningoencephalitis had kidneys, the pancreas, one lung and the liver transplanted, with no recipient infectious complications (C). (83) Also, Zibari et al published their experience with 599 donors with positive blood cultures (7.5% of the cases) and urine cultures (4.5% of the cases).…”
Section: Infection Aspectsmentioning
confidence: 99%